Use of Specifically Tailored Chelating Polymers for Boron Removal from Aqueous Solutions by Polymer Enhanced Ultrafiltration - Aydoğan, Ni̇hal; Doganay, Ceren; Yilmaz, Levent; Bicak, Niyazi; Ozbelge, H. Onder (Informa UK Limited, 2011)
Two selective functional polychelatogens, namely hydroxyethylaminoglycerol functioned poly(glycidylmethacrylate (PNS) and Poly(4-Vinyl-1,3-dioxalan-2-one-co-vinyl acetate) (COP) were synthesized and utilized in polymer-enhanced ultrafiltration (PEUF) to remove boron from the aqueous solution. The effect of operating parameters on boron retention was investigated. PNS was synthesized in three molecular weights to observe the effect of molecular weight in borate retention. Increase in pH increased boron retention for all of the synthesized polymers. Decrease in loading resulted in an enhancement in retention values when COP, medium (PNSM) and the low molecular weight of PNS (PNSL) were used. No significant change was observed in the permeate flux with COP (41 L/m2 · h), PNSL (48 L/m2 · h) and PNSM (47 L/m2 · h). However, a decrease in the loading led to a decrease in the permeate flux for high molecular weight PNS (PNSH). Conformational changes in the polymer structure were examined using dynamic and static...